Concurrent Adjacent Merkel Cell Carcinoma and Chronic Lymphocytic Leukemia without Simultaneous Merkel Cell Polyomavirus Detection: A Case Series - Rayan Saade; Saleh Najjar; Mustafa Erdem Arslan; Peter Rady; Stephen K. Tyring; Tipu Nazeer (MDPI AG, 2021)
Background: The association between Merkel cell carcinoma (MCC) and chronic lymphocytic leukemia/small lymphocytic leukemia (CLL/SLL) is well established in the literature. A majority of MCCs are known to be associated with Merkel cell carcinoma polyomavirus (MCPyV), which is postulated to be a possible causative agent linking these two entities. We aim to identify the presence of MCPyV in patients with concurrent adjacent MCC and CLL/SLL. Methods: Archived pathology materials of three cutaneous or surgical excisions with concurrent MCC and CLL/SLL were reviewed. Additional 12-µm sections from paraffin-embedded tissue of these resections were matched with original hematoxylin and eosin-stained slides and used to extract foci from each tumor separately. DNA was extracted from these tissues, and polymerase chain reaction (PCR), utilizing a primer set within a highly conserved "small T" viral DNA region, was done to detect MCPyV. Results: Out of 140 cases of cutaneous or surgical excisions with MCC identified in our electronic medical records (EMR), three had coexisting neighboring CLL/SLL in the same resection specimen. In one case out of three, MCPyV was detected in MCC but not in CLL/SLL. The remaining two cases showed no detection of MCPyV in either MCC or CLL/SLL. Conclusion: MCPyV was not concurrently associated with adjacent MCC and CLL/SLL, indicating that it is not driving simultaneous tumorigenesis, at least in a subset of these cases.